Analysis of Corrosion Resistance and Hardness of Iron Based on Paint Layer Variations on Car Chassis - Anindya Kasih; Ahmad Azzamahsyari; Maulidiah Insani; Susi Umaroh (Automotive Innovations Journal, 2026)
Iron materials are widely used in engineering applications, especially in the automotive industry. However, iron is highly susceptible to corrosion when exposed to aggressive environments. Surface coating using paint is a common and practical method to improve corrosion resistance. Nevertheless, the effectiveness of the number of paint layers on corrosion resistance, changes in material thickness, and hardness characteristics in the context of learning practicums still needs to be evaluated systematically. This study aims to analyze the effect of the number of paint layers on iron materials through an experimental approach based on practical work. Four iron specimens were used, consisting of one uncoated sample as a control and three samples with one, two, and three layers of paint applied to one surface. The thickness of the material was measured using calipers and an ultrasonic thickness gauge. Corrosion testing was carried out by immersing the samples in an HCl solution for 24 hours, followed by measuring the change in mass and calculating the corrosion rate. Hardness testing was only carried out on uncoated samples using a portable Leeb hardness tester. The research data was obtained from three practical groups and analyzed comparatively. The results showed that an increase in the number of paint layers caused an increase in the thickness of the iron material. Corrosion testing showed that uncoated samples had the highest corrosion rate, while painted samples experienced a decrease in corrosion rate as the number of layers increased. In addition, an inverse relationship between material thickness and corrosion rate was identified. Hardness test results on uncoated samples showed relatively uniform values, indicating the initial mechanical properties of the material were homogeneous. Consistent results were obtained in all three practical groups despite numerical variations. It can be concluded that the number of paint layers affects the thickness of the material and the corrosion resistance of iron in the context of practical work. Painting has been proven to be effective in reducing the rate of corrosion, with the level of protection increasing as the number of layers increases. The consistency of results between groups shows that the testing method used is suitable for comparative analysis in the Technical Materials Workshop practical activities